CONSISTENCY OF TBUT VS NIBUT MEASUREMENT FOR ASSESSMENT OF DRY EYE DISEASE IN COMPUTER VISION SYNDROME: Oral Presentation - Observational Study - Resident - ANGELINA SURYA TALLO (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : The coronavirus disease (COVID-19) pandemic requires medical faculty students to attend distance lectures using computers for long periods of time which directly has an impact of computer vision syndrome (CVS) which can progress to dry eye disease (DED). One of the tear film stability tests is the Tear Break Up Time, both with the invasive tear break up time (TBUT) technique and the non- invasive tear break up time (NIBUT) technique. This study aims to determine the consistency of tear film stability measurements using these two techniques in medical faculty students who suffer from CVS with and without DED. Methods : 62 medical students of Udayana University were enrolled in this study and devided into two groups namely CVS with DED symptoms and CVS without DED symptoms. Both groups were underwent TBUT examination using fluorescein strips and cobalt blue filter with slitlamp biomicroscopic and NIBUT examination with the tear film analysis software from Medmont E300 corneal topography. Results : There was no significant difference between TBUT and NIBUT measurements in the DED group (p=0.1985) and in the Non-DED group (p=0.9336). There was no difference in the consistency of TBUT and NIBUT in the two groups (p=0.4550). Conclusion : Both techniques provide consistent results in assessing DED. NIBUT technique is faster and more convenient for patients also can be an alternative for practitioners to diagnose DED if it is not possible to use TBUT due to allergies or the unavailability of fluorescein at the clinic.